The architecture of hydrogen and sulfur σ-hole interactions explain differences in the inhibitory potency of C-β-d-glucopyranosyl thiazoles, imidazoles and an N-β-d glucopyranosyl tetrazole for human liver glycogen phosphorylase and offer new insights to structure-based design. Issue 1 (1st January 2020) - Kyriakis, Efthimios; Karra, Aikaterini G.; Papaioannou, Olga; Solovou, Theodora; Skamnaki, Vassiliki T.; Liggri, Panagiota G.V.; Zographos, Spyros E.; Szennyes, Eszter; Bokor, Éva; Kun, Sándor; Psarra, Anna-Maria G.; Somsák, László; et al.
Graphical abstract: Highlights: C -Glucopyranosyl imidazoles, thiazoles, N -glucopyranosyl tetrazole GP inhibitors. The most potent with a 2-naphthyl substituent, displays a K i value of 3.2 µM. Inhibitors display potency in HepG2 cells. The architecture of hydrogen bond or sulfur σ-hole bond interactions provide SAR. Abstract: C -Glucopyranosyl imidazoles, thiazoles, and an N -glucopyranosyl tetrazole were assessed in vitro and ex vivo for their inhibitory efficiency against isoforms of glycogen phosphorylase (GP; a validated pharmacological target for the development of anti-hyperglycaemic agents). Imidazoles proved to be more potent inhibitors than the corresponding thiazoles or the tetrazole. The most potent derivative has a 2-naphthyl substituent, a K i value of 3.2 µM for hepatic glycogen phosphorylase, displaying also 60% inhibition of GP activity in HepG2 cells, compared to control vehicle treated cells, at 100 μM. X-Ray crystallography studies of the protein – inhibitor complexes revealed the importance of the architecture of inhibitor associated hydrogen bonds or sulfur σ-hole bond interactions to Asn284 OD1, offering new insights to structure-based design efforts. Moreover, while the 2-glucopyranosyl-tetrazole seems to bind differently from the corresponding 1, 2, 3-triazole compound, the two inhibitors are equipotent.